Is Hydrogen Sulfide a Concern During Treatment of Lung Adenocarcinoma With Ammonium Tetrathiomolybdate? - Li, Xiang; Li, Na; Huang, Li; Xu, Shi; Zheng, Xue; Hamsath, Akil; Zhang, Mei; Dai, Lijun; Zhang, Hui; Wong, Justin Jong-Leong; Xian, Ming; Yang, Chun-tao; et al. (Frontiers in Oncology, 2020)
Ammonium tetrathiomolybdate (ATTM) has been used in breast cancer therapy for copper chelation, as elevated copper promotes tumor growth. ATTM is also an identified H2S donor and endogenous H2S facilitates VitB12-induced S-adenosylmethionine (SAM) generation, which have been confirmed in m6A methylation and lung cancer development. The m6A modification was recently shown to participate in lung adenocarcinoma (LUAD) progression. These conflicting analyses of ATTM’s anticancer versus H2S’s carcinogenesis suggest that H2S should not be ignored during LUAD’s treatment with ATTM. This study was aimed to explore ATTM’s effects on LUAD cells and mechanisms associated with H2S and m6A. It was found that treatment with ATTM inhibited cell growth at high concentrations, while enhanced cell growth at low concentrations in three LUAD cell lines (A549, HCC827 and PC9). However, another copper chelator triethylenetetramine, without H2S releasing activity, was not found to induce cell growth. Low ATTM concentrations also elevated m6A content in A549 cells. Analysis of differentially expressed genes in TCGA cohort indicated that m6A writer METTL3/14 and reader YTHDF1 were upregulated while eraser FTO was downregulated in LUAD tissues, consistent with the findings of protein expression in patient tissues. ATTM treatment of A549 cells significantly increased METTL3/14 and YTHDF1 while decreased FTO expression. Furthermore, inhibition of m6A with shMETTL3 RNA significantly attenuated eukaryotic translation initiation factor (eIF) expression in A549 cells. Correlation analysis with TCGA indicated that small nuclear ribonucleic protein PRPF6 was positively expressed with YTHDF1 in LUAD tissues. Knockdown of YTHDF1 partially blocked both basal and ATTM-induced PRPF6 expression, as well as A549 cell growth. Lastly, ATTM treatment not only raised intracellular H2S content but also upregulated H2S-producing enzymes. Exogenous H2S application mimicked ATTM’s aforementioned effects, but the effects could be weakened by zinc-induced H2S scavenging. Collectively, H2S impedes ATTM-induced anticancer effects through YTHDF1-dependent PRPF6 m6A methylation in lung adenocarcinoma cells.